Effect of Sintering Temperature on Electrical and Microstructure Properties of Hot Pressed Cu-TiC Composites - Islak, S.; Kir, D.; Buytoz, S. (Int Inst Science Sintering (I I S S), 2014)
In this study, Cu-TiC composites were successfully produced using hot pressing method. Cu-TiC powder mixtures were hot-pressed for 4 min at 600, 700 and 800 degrees C under an applied pressure of 50 MPa. Phase composition and microstructure of the composites hot pressed at different temperatures were characterized by X-ray diffraction, scanning electron microscope, and optic microscope techniques. Microstructure studies revealed that TiC particles were distributed uniformly in the Cu matrix. With the increasing sintering temperature, hardness of composites changed between 64.5 HV0.1 and 85.2 HV0.1. The highest electrical conductivity for Cu-10 wt.% TiC composites was obtained for the sintering temperature of 800 degrees C, with approximately 68.1 %IACS.
Keywords: Cu-TiC composites; Electrical conductivity; Microstructure; Sintering temperature